Dengue virus infection of mice: Morphology and morphogenesis of dengue type 2 virus in suckling mouse neurones - S. Sriurairatna (2018)
In dengue type 2 virus infected neurones of suckling mice, formation of single membrane vesicles is observed in the distended cisternae of the endoplasmic reticulum mostly of the perinuclear zone around 72 h after inoculation. Electron dense 50 nm virus particles are arranged in chains in these distended cisternae; some form small crystalloid aggregates. Aberrant particles of different shapes are also seen in the distended cisternae about the same time that the virus particles appear. Parallel filamentous structures are occasionally observed in the cisternae that contain very few virions, either characteristic or aberrant. Increasing cytopathic changes are present after 75 to 96 h. There is an intense vesicular formation. Large numbers of virions and aberrant particles are seen either in the endoplasmic reticulum cisternae or smooth membrane vesicles. They are spread throughout the neurocytoplasm, extending into the dendrites. Dengue virions which are enclosed in fairly intact membrane bound vesicles are released during cytolysis of the neurones. Morphogenesis of dengue virus type 2 is discussed.